Bridging Clinical Gaps: How Pharmaceutical Sciences Are Transforming Medical Practices - Hastutik, Widya (Journal of Community Health Provision, 2025)
This study explores how pharmaceutical sciences are transforming medical practices by bridging clinical gaps through innovative drug development. By focusing on advancements in personalized medicine, biologics, targeted therapies, and drug delivery systems, the research highlights how these innovations are improving patient outcomes, reducing healthcare costs, and enhancing treatment efficiency. The findings show a significant reduction in mortality and morbidity rates, shortened hospital stays, and improved drug adoption rates, underscoring the effectiveness of modern pharmaceutical advancements in medical practice. Through a comprehensive analysis, this study contributes to understanding how pharmaceutical sciences can address critical clinical challenges and offers insights into future medical practices.